Phát triển mô hình nước nông ba lớp và áp dụng vào dự báo chuyển động bão trên vùng biển Việt Nam - Đức, Lê; Xin, Kiều Thị (Vietnam Journal of Earth Sciences, 2003)
Developing and implementing a three-layer shallow water model for forecasting motions of tropical cyclones over the Sea region of Vietnam